PEMBELAJARAN MENULIS CERPEN MENGGUNAKAN METODE PICTURE AND PICTURE - ahyar hidayat; wikanengsih wikanengsih; diena san fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Abstract               Learning to write short stories is generally always considered difficult learning by students because of the difficulty in adjusting the theme to the title when writing stories and the difficulty in pouring their imagination into written language. There is a problem formulation in the research, namely regarding the difficulties of students in writing short stories. This study aims to answer the formulation of problems regarding students' difficulties in writing short stories. This research was conducted on 23 students of class XI at SMK 4 LPPM RI Padalarang. This research method uses descriptive qualitative by using data collection techniques through writing skills tests. Based on the results of the research, during the learning activities to write short stories with the picture and picture method, there is an average value in the initial test of 64.13 and an average value of 78.7 in the final test Keywords: Learning, Short Story Writing, Picture and Picture